2012
DOI: 10.1007/s11064-012-0823-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Trehalose on PC12 Cells Overexpressing Wild-Type or A53T Mutant α-synuclein

Abstract: Accumulation of α-synuclein (α-Syn) is a common pathology for both familiar and sporadic Parkinson's disease (PD), enhancing its clearance might be a promising strategy for treating PD. To assess the potential of trehalose in this regard, we investigated its effect on the PC12 cells overexpressing wild type (WT) or A53T mutant α-Syn and the implicated pathway it might mediated. We observed that trehalose promoted the clearance of A53T α-Syn but not WT α-Syn in PC12 cells, and confirmed the increased LC3 and Ly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 75 publications
(61 citation statements)
references
References 33 publications
2
58
0
Order By: Relevance
“…Our previous work reported that trehalose was effective in disaggregating mutant α-synuclein protofibrils and inhibiting the formation of mutant α-synuclein fibrils in the cell-free system of A53T α-synuclein incubation [30]. Further research confirmed that trehalose could enhance clearance of α-synuclein aggregates through activation of the autophagy pathway [31]. Recently, it has been argued that, given advances in animal Fig.…”
Section: Discussionmentioning
confidence: 93%
“…Our previous work reported that trehalose was effective in disaggregating mutant α-synuclein protofibrils and inhibiting the formation of mutant α-synuclein fibrils in the cell-free system of A53T α-synuclein incubation [30]. Further research confirmed that trehalose could enhance clearance of α-synuclein aggregates through activation of the autophagy pathway [31]. Recently, it has been argued that, given advances in animal Fig.…”
Section: Discussionmentioning
confidence: 93%
“…The human SH-SY5Y neuroblastoma cells possess many characteristics of DAergic neurons, and in the present study SH-SY5Y cells overexpressing A53T α-syn (SH-SY5Y-A53T) were generated for PD research as described previously (Lan et al, 2012). The cDNA for human mortalin (Yang et al, 2011b) was kindly provided by Professor Wen Liu (Department of Cellular and Genetic Medicine, Fudan University, Shanghai, China), subcloned into pLenti6 vector (Invitrogen, USA) and packaged into viral particles according to the manufacturer's instructions (Biowit Technologies, China).…”
Section: Cell Lines and Lentiviral Vectorsmentioning
confidence: 99%
“…After two washes, cells were incubated with secondary antibody (1:100, FITC goat antirabbit IgG, Kangcheng, China) (Qu et al, 2012). A laser scanning microscope (Olympus BX60) was then applied to capture images (Lan et al, 2012).…”
Section: Immunofluorescence Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…The cells showed depressed levels of tau aggregation and much less cytotoxicity. In a related study, Lan et al (2012) showed that production of synuclein (a protein related to Parkinson's disease) was suppressed by trehalose induced autophagy. The authors of both these studies suggested that trehalose might be developed as a therapeutic agent for these diseases, but it is, of course, unclear how such a therapy could be developed for clinical application.…”
Section: Trehalose and Autophagymentioning
confidence: 99%